Efeitos do ácido zoledrônico na consolidação de fraturas da diáfise femoral de ratos - Rocha, Sania Nara Costa da (2011)
Femoral fractures are considered a public health problem and account for a high rate of morbidity and mortality by the occurrence of complications. They occur not only in young patients exposed to major trauma but in the elderly population as well. Most elderly patients have certain conditions, eg, osteoporosis, which further increase the risk of such fractures. Since the trend is that the average age of population increase, the consequences of osteoporosis will increase proportionately. Clinical studies have demonstrated that the use of bisphosphonates reduces the risk of occurrence of fractures in osteoporotic patients. Zoledronic acid belongs to the class of bisphosphonates, currently being considered the most potent. Because the dose that these patients use is an annual basis, there is an increased adherence and persistence of patients in treatment, thereby decreasing the risk of fractures. This study aimed to evaluate the effects of zoledronic acid on bone healing in femurs of rats with reduced Kirshner wire. We used 36 adult male rats, Wistar, weights ranged from 250 to 300g. All animals underwent surgery that was performed on the fracture of the femoral shaft with a blunt guillotine. The animals were divided into two groups: the group of zoledronic acid, which received intraperitoneally 0.1 mg / kg of the acid and the control group. The animals were sacrificed 7, 14 and 28 days postoperatively. There were two deaths from unknown causes. We performed a radiographic study with film mammography to analyze the optical density and area of callus, measured in mm ² and histological study, using samples stained with picrosirius red under dense microscopic light to quantify the formation of collagen type I and type III in the cortical region near the fracture and callus. No significant statistical results regarding the optical density were observed with the use of the zoledronic acid. When conducting a comparative inter-group analyses, the callus area showed no significant differences (p <0.05) in a time of consolidation (7, 14 and 28 days) used in this study. Despite the zoledronate group in 28 days time to have a result very close to the level of significance (p <0.05). In the intragroup analysis there is considerable increase in the natural area of the callus. The percentage of type III collagen in the cortical and callus did not possess significant differences in intragroup analysis and the analysis groups. By contrast this study had significant results in relation to collagen type I. Concluding that zoledronic acid significantly increased the percentage of type I collagen in the callus in healing time of 28 days. And in the cortical bone three times considered (7,14,28 days).